EFFECT OF YERSINIA PSEUDOTUBERCULOSIS TOXINS ON THE BIOFILM FORMATION - N. A. Terenteva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. To study the effect of heat-labile (HLTY) and heat-stable (HSTY) lethal toxins of the of Yersinia pseudotuberculosis on the formation of biofilms by these bacteria. Materials and methods. For the isolation of toxins and the investigation their ability to effect on the biofilm formation there were used the strain of Y. pseudotuberculosis 512 (pYV48Mjl. рУМ82МД) and strain 2517, carrying virulence plasmid pYV and lost it, correspondingly. Results. The stimulation of biofilm formation at 20°C by the strain 2517 (pYV+), carrying virulence plasmid as well as the strain 2517 (pYV-) without plasmid were observed In the presence of HLTY. At low positive temperature (6 - 8°C) HLTY reduces the amount of the formed biofilm. HSTY inhibited the biofilm formation by the both strains of Y. pseudotuberculosis tested during the incubation for 3 days at 20°C and 6 - 8°C. Moreover the extent of inhibition was decreased with temperature decreasing. Conclusion. The both of the Y. pseudotuberculosis protein toxins has been revealed to affect on the biofilm formation by Y. pseudotuberculosis bacteria, however, the impact of HLTY and HSTY in the processes of biofilm formation was shown to be different, and the mechanism of such action of toxinsis under way.